Group Counseling in Exploring Self Potential in Adolescents with Learning Difficulties on Depression - Viryanti, Noerhaliza; Solihah, Ii; Miradwiyana, Bara (Poltekkes Kemenkes Semarang, 2025)
Background: Adolescence is a critical developmental stage characterized by identity formation and heightened vulnerability to academic stress stemming from demanding school tasks, competitive learning environments, and pressure for high achievement. These stressors may contribute to depressive symptoms, which can impair concentration, memory, social functioning, and academic outcomes. Globally, depression affects an estimated 280 million people, with the World Health Organization reporting higher rates among females. These trends underscore the need for effective and accessible mental-health interventions for adolescents, particularly those experiencing learning difficulties. Purpose: to examine the effect of group counseling focusing on self-potential exploration in adolescents with learning difficulties on reducing depressive symptoms. Methods: A quasi-experimental pre-test–post-test control group design was used. Fifty adolescents participated, with 25 assigned to the intervention group and 25 to the control group. The intervention group received structured group counseling sessions, whereas the control group took part in conventional lecture-based learning support. Depression levels were measured before and after the intervention using a standardized assessment tool. Results: Statistical analysis showed a significant difference in the reduction of depression scores between the intervention and control groups (p = 0.000). Adolescents who received group counseling experienced a greater decrease in depressive symptoms than those in the control group. Conclusion: Group counseling effectively reduces depression among adolescents with learning difficulties by fostering self-expression, emotional awareness, and positive self-potential exploration. Integrating group counseling into school-based mental-health services may strengthen psychological well-being and enhance academic resilience in this population.